PENGARUH WORK LIFE BALANCE, KONFLIK KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN ROKAN HULU - Sri Eka Lestari; Arrafiqur Rahman (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This study aims to determine the effect of work life balance, work conflict and workload on the performance of Rokan Hulu District's Department of Youth and Sports Education. This research is descriptive research. The population of this study were all employees of the Department of Youth Education and Sports in Rokan Hulu Regency. The sampling technique was using a saturated sampling (census) technique with 94 respondents. Data collection methods using observations and questionnaires. The instrument reliability test includes the validity test and the reliability test, the classic assumption test includes the normality test, multicollinearity test and heteroscedasticity test. Data analysis using multiple linear regression analysis using the SPSS program. Partially, the t-work work balance 2,253 is obtained, work conflict is 1,862 and workload is 0.172. Simultaneously, an F-count of 3,838 was obtained. The results showed that 5.8% of performance was influenced by work life balance, work conflict and workload, while the remaining 94.2 was influenced by other variables not examined in this study. The conclusion of this study based on the partial test results is only the work life balance variable that has a significant effect on performance, while simultaneously work life balance, work conflict and workload have a significant effect together on performance.